A pulmonary metastatic model of murine melanoma assessed by magnetic resonance imaging. Issue 7 (21st April 2017) - Numata, Takafumi; Kiryu, Shigeru; Maeda, Tatsuo; Egusa, Chizu; Tsuboi, Ryoji; Harada, Kazutoshi
Abstract: Immune checkpoint inhibitors and kinase inhibitors have improved prognosis of malignant melanoma (MM) patients. However, these therapies cannot completely overcome the metastasis of MM. Thus, development of new therapy against metastasis should be required. A first step towards this goal, the aim of this study, is to establish a model of pulmonary metastasis from primary cutaneous MM and a monitoring system. B16‐F10, a murine melanoma cell line, was subcutaneously injected into the pinna of mice. The pinna was excised when the lesion was detected. A metastatic nodule on T2‐weighted imaging was detected 4 weeks after resection of the pinna. Lung metastases were observed in 37.5% (6/16) of the specimens. We established a novel murine model of the high pulmonary metastasis of MM. The MRI was useful for observations of the growth of the metastatic lesions in the lungs without dissection.